Assessing the impact of AUKUS and its strategic implications for ASEAN’s regional security - Mohamed, Ahmad Shah Pakeer; Mustafa , Mohammad Nurfadli Azamuddin; Abdul Batau, Mohamed Fajil; Sulaiman , Sulhairil Hafiz; Md Ladin, Mohd Rizam (Journal of Islamic, Social, Economics and Development, 2025)
The formation of AUKUS, a trilateral security alliance between Australia, the United Kingdom, and the United States, has introduced a significant transformation in the strategic landscape of the Indo-Pacific region. Officially announced in September 2021, the pact aims to strengthen Australia’s defense capabilities, particularly through the acquisition of nuclear-powered submarines, as a strategic response to the growing influence of China. While AUKUS is presented as a mechanism to uphold a rules-based international order and promote regional stability, its broader implications for the Association of Southeast Asian Nations (ASEAN) are complex and multifaceted. This study critically examines the impact of AUKUS on ASEAN’s regional security framework, focusing on both the challenges and opportunities it presents. Key concerns include the potential for an arms race, increased militarization, and the risk of internal divisions among ASEAN member states due to differing strategic alignments with global powers. Furthermore, the emergence of AUKUS raises questions about ASEAN’s centrality and its capacity to maintain a neutral, inclusive, and cohesive regional security architecture. Conversely, AUKUS may serve as a catalyst for ASEAN to reassess its security strategies, strengthen intra-regional cooperation, and enhance resilience against external pressures. By analyzing the diverse responses of ASEAN member states, this research underscores the need for unified and adaptive approaches to navigate the evolving geopolitical environment. The findings highlight ASEAN’s pivotal role in maintaining peace, stability, and strategic balance in the Indo-Pacific amid intensifying competition among major powers.